Oralidade na literatura: turnos conversacionais em diálogos literários construídos por Rubem Fonseca - Gomes, Tiago Moreira (2017)
Academic studies about spoken language expression on the written and in Literature have lead articles, papers and thesis, whose objetcs of study have been, in the most time, chronic and theater plays. The short story has been few studied by the theories that intend to analize the spoken language. The objetive of this work is to analysis the spoken languagem expression, in literary dialogues, specially the short-story, based on Conversation Analysis. At this study, we checked how happen the micro and macro organizations of the dialogues analysis and how the interactional process happen among the speakers, specificly, the turns change among fictional texts caracters. The Corpus is constituted for a contemporary short story, O gravador, by Rubem Fonseca. We may give preference to a short story of Century XX because of its contemporarity and because it shows examples closer of our presente-day reality. To reach our objectives, we lean on theorics like Kerbrat-Orecchioni (2006), Marcuschi (1986), Preti (2001, 2004, 2005 e 2011), among others. Our analyses let us to prove that the short-atory is an example of hybrid genre, since it shows its own caracteristics of spoken, allied to the written language, and it may be example of the communications competence modals close of a natural dialogue. We hope, with the results presented here, help to the studies about Spoken and Written Language